Ravindranath Tagore rachnavali/ Drishtidaan tatha anya kahaniyan - Tagore, Ravindra Nath; Edited by Indra Nath Chaudhury (New Delhi Sasta Sahitya Mandal, 2020)
Novel
Keywords: Hindi novel; Noble prize winner Ravindranath Tagore